PERSEPSI PELATIHAN, SIKAP KERJA DAN MOTIVASI TERHADAP KUALITAS SUMBER DAYA MANUSIA PADA YAYASAN PONDOK PESANTREN ROUDLOTUT THOLIBIN BALEN BOJONEGORO - jurnalmap map; Siti Ismawati; Woro Utari; Cathrine Sri Hartati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT The purpose of this study is to describe the perception of training, work attitude, motivation and quality of human resources. And then to analyze the influences of perception of training, work attitude and motivation both partially and simultaneously on human resources quality at Radulotut Tholibin Balen Bojonegoro Ponpes Foundation. The type of this research is explanatory research and the population in this study is all employees of the Foundation Ponpes Roudlotut Tholibin Balen Bojonegoro with the number of employees as many as 35 people. The results showed that the condition of training perception, work attitude, motivation and quality of human resources at the Foundation Roudlotut Tholibin Balen Bojonegoro Ponpes in good category. The perception of training, work attitude and motivation simultaneously have a significant influence on the quality of human resources. Perception of training, work attitude and motivation partially have a significant influence on the quality of human resources. The perception of training has a dominant influence on the quality of human resources at the Roudlotut Tholibin Balen Bojonegoro Ponpes Foundation. Keywords: training, work attitude, motivation, human resources quality